Supporting healthcare workers in vaccination efforts - Shira Ramot; Orna Tal (Taylor & Francis Group, 2023)
Encouraging healthcare workers (HCWs) to be vaccinated is a global challenge and plays a fundamental role in combating COVID-19 pandemic. Beyond national policy, which could be different between countries, the decision to be vaccinated involves personal opinions, values, risk perception and attitudes. HCWs may have their own concerns and fears about vaccination beyond being part of the health system. They have a national role in encouraging public vaccination and therefore we recommend strengthening their involvement as policy agents. The health system should equip HCWs with information on the nature and scope of circulating concerns in their communities. At the same time, be attentive to their concerns, equip them with established knowledge and work to strengthen their confidence in the vaccine.